Economic Level Of Real Water Losses In Water Distribution System Using Minimum Night Flow Statistical Model - Alkasseh, Jaber M. A. (2013)
Minimum night flow (MNF) is a common method used to evaluate water loss in a water network. In 2011, the average percentage of non-revenue water (NRW) for the state of Perak in Malaysia was 30.4 %, a figure which resulted in major financial, supply, and pressure losses, as well as excessive energy consumption. In this study, the appropriate time band of MNF and the actual water loss or amount of NRW for the district of Kinta in Perak, Malaysia were investigated. Flow and pressure for 361 zones were monitored for 24 h by the Perak Water Board (Lembaga Air Perak, LAP) using PrimeWorks software (version: 1.5.57.0). Ninety study zones were randomly selected from 361 zones. The 90 study zones were divided into three groups, with each group having 30 zones. Data on the minimum value of flow in 2010 were screened within the time band of 1:00 am to 5:00 am. The frequency of MNF occurrences was analysed every 15 minutes. Results of the study revealed that the majority (85%) of MNF frequencies in the 90 study areas were found at the time band 2:30 am to 4:30 am, whereas 95% of the frequencies were at time band 1:45 am to 4:45 am; therefore, the mean MNF for each zone in 2010 was determined to be between 1:00 am and 5:00 am. Furthermore, a statistical analysis of the characteristic of water distribution network and a modelling of MNF were carried out to estimate water loss in Kinta District, Perak. Factors for physical, hydraulic, and operational variables were selected and correlated with MNF (L/s).